THE USAGE OF MULTI-LEVEL PRACTICAL TRAININGS TO FORM CULTURE OF SAFE LIFE AND ACTIVITY OF STUDENTS - Gvozdii, Svitlana P. (Educological discourse, 2015)
Relevance of the work caused by the situation in the east of Ukraine and the need for fast and high-quality training on safety. The author’s technique is suggested of multi-level practical training, which is defined as connected with the life of intensive training with practical working of certain abilities and skills of teachers and students in school and beyond. It’s given an example of the usage of multi-level practical training to form a culture of safe life and activity of students. The author gives a definition of «culture of safe life and activity». It is proved the effectiveness of the proposed methodological approach in teaching safety issues and its further usage in higher educational institutions of Ukraine.